Ficus hirta Vahl. Ameliorates Nonalcoholic Fatty Liver Disease through Regulating Lipid Metabolism and Gut Microbiota. (10th May 2022) - Quan, Ting; Zhou, Fangyu; Chen, Huiyuan; Jian, Lina; Yang, Yuxuan; Xia, Fan; Xiang, Shijian; Zhou, Benjie; Li, Shasha
Abstract : Nonalcoholic fatty liver disease (NAFLD) has gradually become one of the most serious liver diseases threatening human health in the world. Currently, Chinese herbal medicine is a potentially important treatment option for NAFLD, and the development of effective Chinese herbal medicine has a good prospect. Previous studies have suggested that Ficus hirta Vahl. (FV) has various protective effects on the liver. In this study, we investigated the therapeutic outcomes of FV treatment for the liver disease and its underlying mechanism using HepG2 cell lines induced by palmitate (PA) and mouse model fed with high-fat diet (HFD). FV mainly exerts pharmacological effects by mediating lipid metabolism and inflammation. During the lipid metabolism regulation process, CD36, SREBP-1, SCD1, PPAR γ, ACOX1, and CPT1 α are the key factors related to the healing effects of FV on NAFLD. During the inflammation process, the downregulation of IL-6, IL-1 β, and TNF- α is involved in alleviation of NAFLD. Furthermore, CD36 overexpression promotes lipid abnormal metabolism and inflammation in PA-induced HepG2 cells, while CD36 knockdown and FV supplementation reverse these responses. In addition, FV also modulates gut microbiota composition, such as Allobaculum, Faecalibaculum, and Butyricicoccus in HFD-fed mice. In summary, our findings demonstrated that FV exerted a beneficial preventive and therapeutic effect on NAFLD by improving lipid metabolism and inflammation as well as regulating the structure of gut microbiota, and therefore, FV may be a candidate for the treatment of NAFLD.